2020
DOI: 10.1016/j.ejca.2020.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Age-, sex- and disease subtype–related foetal growth differentials in childhood acute myeloid leukaemia risk: A Childhood Leukemia International Consortium analysis

Abstract: Background: Evidence for an association of fetal growth with acute myeloid leukemia (AML) is inconclusive. AML is a rare childhood cancer, relatively more frequent in girls, with distinct features in infancy. In the context of the Childhood Leukemia International Consortium (CLIC), we examined an a priori hypothesis that the association may vary by age, sex and disease subtype using data comprising 22 studies and a total of 3564 AML cases.Methods: Pooled estimates by age, sex and overall for harmonized fetal g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 59 publications
0
9
1
Order By: Relevance
“…By contrast, the evidence on the association between birth weight and childhood AML is more heterogeneous with both pooled and meta-analyses suggesting a U-shaped association [17,29,31]. However, a recent CLIC study found a positive association for AML with high birth weight and with being large-for-gestational-age but no indication of a U-shaped association [42].…”
Section: Results In the Context Of Previous Studiesmentioning
confidence: 97%
“…By contrast, the evidence on the association between birth weight and childhood AML is more heterogeneous with both pooled and meta-analyses suggesting a U-shaped association [17,29,31]. However, a recent CLIC study found a positive association for AML with high birth weight and with being large-for-gestational-age but no indication of a U-shaped association [42].…”
Section: Results In the Context Of Previous Studiesmentioning
confidence: 97%
“…It was established in 2007 with the goal of overcoming the limitations of single epidemiological studies and allowing the assessment of relatively infrequent potential risk factors, including specific nonchromosomal birth defects. Further comprehensive descriptions of CLIC have been published previously 25‐31 …”
Section: Methodsmentioning
confidence: 99%
“…We used logistic regression models to calculate odds ratios (OR) and 95% confidence intervals (CI) for each birth defect‐leukemia combination, while adjusting for the following variables: study site, sex, birthweight (<2500; 2500‐3999; >3999 g), gestational age (preterm [<37 weeks]; term [≥37 weeks]), maternal age (<25; 25‐29; 30‐34; 35‐39; ≥40 years), birth year and child's ethnicity (non‐Hispanic White; non‐Hispanic Black; Hispanic; and other —these categories varied by study and were harmonized based on previous CLIC assessments) 29,30,36 . These variables were selected based on previous assessments and to be consistent with other studies evaluating associations between nonchromosomal birth defects and pediatric cancer 10,26‐31 . Additionally, the categorical variables were designed similarly to what was used in previous CLIC assessments 27‐30 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations